Comorbid Tuberculosis in the Context of the Formation of a Local Epidemic Situation - V. M. Kolomiets; N. A. Polshikova; A. Yu. Petrov; A. L. Kovalenko; M. A. Alymenko; E. V. Talikova (Антибиотики и Химиотерапия)
The aim of the study was to analyze epidemiological data on tuberculosis in the Kursk region, taking into account the changing socio-economic situation in the region, as well as to study the possibilities of using remaxol in the regimens of accompanying therapy for hepatotoxic reactions in patients with tuberculosis. During the analysis of the data array, it was noted that the dynamics of infectious processes were similar to the other regions of the Russian Federation: a decrease against the background of COVID-19 and a gradual increase in morbidity in the post-pandemic period. A third of the patients included in the study were diagnosed with comorbid forms of tuberculosis, characterized by greater severity of the disease and lower effectiveness of therapy: recovery (with deregistration) was recorded in half (49.8%) of patients with monoinfection, while in patients with a comorbid course of the disease, this figure was 35%. At the same time, clinical recovery was diagnosed in 38.2% of patients with monoinfection and in 47% of patients with comorbid tuberculosis (P<0.5). The inclusion of remaxol (intravenous drip, 400 ml/day, every other day — course No. 5, then 1 time per week No. 4) in the treatment regimens for hepatotoxic reactions during the main course of treatment in patients with tuberculosis, in both monoinfection and comorbid forms, contributed to a more rapid relief of deviations in clinical and laboratory parameters and an increase in the effectiveness of treatment: 84.2% in patients with tuberculosis and 85.7% with a comorbid form of tuberculosis versus 81.9% and 83.7% in patients in the comparison group (P≤0.05).